Excavations at the Classical-Period Settlement of Artyushchenko-1 (Bugazskoye) on the Taman Peninsula - Vinogradov, Yurij A.; Lebedeva, Elena V. (Hyperboreus, 2006)
A survey of the excavations of Artyushchenko-1 (Bugazskoye) on the Taman Peninsula.